Preparation method and application of composite nanomaterial NCDs / ZnFe2O4 for degrading Rh B

Preparation of NCDs/ZnFe2O4 nanocomposites by hydrothermal method solves the shortcomings of the preparation method of ZnFe2O4 composites in the prior art, improves the photocatalytic activity and particle size uniformity of the material, and achieves efficient photocatalytic performance and simplified preparation process.

CN119303606APending Publication Date: 2025-01-14WUHAN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310847157.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-11
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing preparation methods of ZnFe2O4 composite materials have problems such as low yield, insufficient particle size and morphological uniformity, high raw material cost and use of harmful solvents, which limit their application in the field of photocatalysis.

Method used

The NCDs powder was mixed with ZnFe2O4 aqueous solution by hydrothermal method, and then the NCDs/ZnFe2O4 nanocomposite was obtained by centrifugation and drying, which simplified the preparation process and improved the crystallinity and particle of the material. Diameter uniformity.

Benefits of technology

The photocatalytic activity and electron transfer capability of NCDs/ZnFe2O4 materials are improved, the efficiency of degrading wastewater in solar light is enhanced, and the preparation process is simplified and the cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119303606A_ABST
    Figure CN119303606A_ABST
Patent Text Reader

Abstract

The invention relates to a method for preparing an NCDs / ZnFe2O4 composite nano material. The method has theoretical and practical significance for constructing a novel photocatalytic material which has efficient photocatalytic activity and is economical and environment-friendly. The method comprises the following steps: firstly, preparing NCDs by utilizing a hydrothermal method to obtain solid powder of the NCDs; and then, further preparing the NCDs / ZnFe2O4 composite nano material by virtue of a hydrothermal method. The NCDs / ZnFe2O4 nano composite material prepared by the method has excellent photocatalytic performance, good photochemical stability and relatively high photocatalytic activity, and can be applied to the environmental governance fields of degradation of wastewater, organic pollutants and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material preparation, and relates to a NCDs / ZnFe2O4 nanocomposite material composite material prepared by a hydrothermal method and a preparation method thereof. Background Art

[0002] In recent years, spinel ferrite and its composite materials have attracted people's attention in the field of environmental protection due to their unique optical and electrical properties. They are mainly used to degrade toxic pollutants in wastewater. In wastewater treatment, spinel ferrite exhibits characteristics such as narrow band gap and stability. Since 46% of the light energy in sunlight is in the visible light region, spinel ferrite nanoparticles with narrow band gaps (such as CoFe2O4 is 2.31eV and ZnFe2O4 is 1.9eV) are more suitable for using solar energy to photocatalytically degrade pollutants than traditional semiconductors TiO2 (3.2eV) and ZnO (3.2eV). ZnFe2O4 in ferrite materials has also been widely studied and applied due to its excellent performance. Zinc ferrite has many excellent properties: (1) Zinc ferrite is a soft magnetic material with excellent performance and a catalyst for the oxidative dehydrogenation of butene; (2) Zinc ferrite has high photocatalytic activity and is a semiconductor catalyst sensitive to visible light; (3) ZnFe2O4 can be produced from industrial waste. The method of preparing ZnFe2O4 by recycling solid waste is a low-cost preparation method; (4) Modification of zinc ferrite can significantly improve the photocatalytic activity of zinc ferrite. ZnFe2O4 has become a research hotspot for many researchers due to its excellent electrical, dielectric, magnetic, chemical and optical properties. This material has important application value in the fields of photocatalysis, electrocatalysis, sensors and biomedicine, but zinc ferrite itself has some disadvantages, such as (1) pure ZnFe2O4 has rapid recombination of photogenerated electron-hole pairs, photocorrosion and low photostability (2) low separation efficiency of photogenerated carriers. These defects limit its application in photocatalysis. The preparation of zinc ferrite with better performance is crucial to obtain new photocatalytic materials.

[0003] The performance of zinc ferrite in the field of photocatalysis has attracted much attention, and surface / structural modification of zinc ferrite is one of the important ways to improve its performance. The modification methods mainly include precious metal deposition, metal ion doping, composite modification, crystal surface control, dye sensitization, quantum dot sensitization, etc. The so-called "quantum dot sensitization" refers to the formation of a heterojunction by doping photocatalysts with quantum dots. Its physical and chemical properties are not simply added, but supplemented on the original physical and chemical properties of the material to achieve the purpose of improving the photocatalytic efficiency.

[0004] Combining semiconductors with various carbonaceous materials, carbonaceous-based composites can tune the band gap of semiconductors and develop visible light-active photocatalysts. However, despite their excellent adsorption capacity, the commercial-scale acceptance of these carbon-supported semiconductors is still limited due to the insufficient efficiency of visible light absorption and charge separation. In addition, carbonaceous precursors such as carbon nanotubes, graphite and their derivatives are mostly expensive and non-renewable, which can significantly improve the photocatalytic activity of photocatalysts.

[0005] At present, there are many methods for preparing ZnFe2O4 composite materials, such as solvothermal method, deposition method, solution-gel method, etc. However, the yield of the solvothermal method is low, and the uniformity of the particle size and morphology of the product still needs to be further improved; the precipitation method still has challenges in exploring suitable precipitation conditions to control the morphology and grain size of the precipitate to obtain ideal catalytic performance; the solution-gel method is still faced with high raw material costs, a large number of micropores in the gel, which leads to significant shrinkage of the gel material during the drying process, and is prone to produce organic solvents that are harmful to the human body. Therefore, it is necessary to find a new green, safe, simple and excellent performance zinc ferrite composite material preparation method. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a NCDs / ZnFe2O4 material with excellent photocatalytic performance and a preparation method and application thereof in view of the above-mentioned deficiencies in the prior art.

[0007] In order to solve the above technical problems, the technical solution provided by the present invention is:

[0008] Provided is an NCDs / ZnFe2O4 material. First, a proper amount of NCDs powder is added to a ZnFe2O4 aqueous solution. At room temperature, the mixed solution is ultrasonically cleaned for 15 minutes to be evenly mixed. Then, it is stirred by a magnetic stirrer to be fully mixed. Then, it is transferred to a high-pressure hydrothermal reactor, heated at a certain temperature for a period of time, cooled to room temperature after the reaction is completed, and solid-liquid separation is performed by a high-speed centrifuge to obtain a composite material solid sample. Then, the solid sample is placed in an oven for drying to finally obtain an NCDs / ZnFe2O4 nanocomposite material.

[0009] According to the above scheme, NCDs of different masses are compounded with ZnFe2O4, and the mass ratios are 1wt%, 3wt%, 5wt% and 7wt% respectively.

[0010] According to the above scheme, NCDs / ZnFe2O4 with different mass ratios were heated in a high-pressure hydrothermal reactor for 2h, 4h, 6h, 8h and 10h respectively.

[0011] According to the above scheme, the sample after the reaction was centrifuged at a speed of 8000 r / min for 10 min in a high-speed centrifuge to separate the solid and liquid to obtain a composite material solid sample.

[0012] According to the above scheme, the concentration of ZnFe2O4 used is 2 mg / ml.

[0013] The present invention also provides a preparation method of the above-mentioned NCDs doping, and the specific steps are as follows:

[0014] 1) Use citric acid solid as a carbon source and add it to distilled water. After ultrasonication for 5 minutes to completely dissolve it, transfer the solution to a high-pressure hydrothermal reactor, add 335 μL of ethylenediamine solution, and then place it in an oven for heating at 200°C for 5 hours. After the reaction is completed, cool it to room temperature to obtain a dark brown NCDs suspension;

[0015] 2) filtering the NCDs suspension in step 1), washing it twice with distilled water, collecting the filtrate, placing it into a 3500MW dialysis bag and dialyzing it for 48 hours, and finally freeze-drying the dialysate to obtain a solid powder of the NCDs sample;

[0016] 3) Add the NCDs sample solid powder material obtained in step 2) and ZnFe2O4 into a high-pressure reactor in a certain proportion, and perform solvent thermal reaction for a certain period of time. After the reaction, wash and dry the powder to obtain the NCDs / / ZnFe2O4 nanocomposite material.

[0017] Preferably, in the step 3), the optimal reaction mass ratio of NCDs to ZnFe2O4 is 3wt%;.

[0018] Preferably, in step 3), the optimal solvent thermal treatment process conditions are: 120° C., heating for 8 hours.

[0019] The present invention also includes the application of the above NCDs / ZnFe2O4 material in environmental management such as degradation of wastewater and organic matter.

[0020] The beneficial effects of the present invention are as follows: 1. The NCDs / ZnFe2O4 material prepared by the present invention shows a higher photocatalytic activity of the ternary photocatalyst under solar spectrum irradiation compared with the binary nanocomposite material. The results show that the introduction of CDs improves the electron transfer ability and the separation efficiency of electron-hole pairs, thereby improving the photocatalytic efficiency and performance of the material. CDs can be used as donors and acceptors, which can effectively improve the electron transfer ability and separate electron-hole pairs, thereby improving the photocatalytic efficiency and performance of the material. In addition, the electronic conductivity and up-conversion photoluminescence performance of CDs also greatly improve the photocatalytic performance of the composite material; 2. The preparation method of the NCDs / ZnFe2O4 material provided by the present invention is simple to operate. The NCDs material is prepared by a simple hydrothermal synthesis route, and the NCDs / ZnFe2O4 material is further synthesized by a hydrothermal method, which simplifies the N doping process and increases the content of doped N, thereby obtaining a NCDs / ZnFe2O4 material with high crystallinity, small particle size, uniform distribution and good water solubility. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0022] Figure 1 PL images of ZnFe2O4 and NCDs / ZnFe2O4 prepared in Example 1 of the present invention;

[0023] Figure 2 These are the EIS graphs of ZnFe2O4 and NCDs / ZnFe2O4 prepared in Example 1 of the present invention.

[0024] Figure 3 This is the transient photocurrent response diagram of ZnFe2O4 and NCDs / ZnFe2O4 prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0025] In order to better understand the present invention, the present invention is further specifically described below through the following examples, but it should not be understood as limiting the present invention. For those skilled in the art, some non-essential improvements and adjustments made according to the above invention content should also be considered to fall within the protection scope of the present invention. Next, the technical solution of the present invention will be further described in conjunction with specific embodiments.

[0026] [Example 1]

[0027] This embodiment provides a method for preparing a ternary composite material NCDs / ZnFe2O4, and the specific steps are as follows:

[0028] 1 g of citric acid solid was added to 10 mL of distilled water, and after ultrasonication for 5 min to completely dissolve it, the solution was transferred to a high-pressure hydrothermal reactor, and 335 μL of ethylenediamine solution was added. The reaction was then heated in an oven at 200 °C for 5 h. After the reaction was completed, the mixture was cooled to room temperature to obtain a dark brown NCDs suspension.

[0029] The NCDs suspension was filtered, washed twice with distilled water, and the filtrate was collected and placed in a 3500MW dialysis bag for continuous dialysis for 48 hours. Finally, the dialysate was freeze-dried to obtain a solid powder of the NCDs sample.

[0030] NCDs powder was added to the ZnFe2O4 aqueous solution to make the mass ratio of 3wt%. The mixture was ultrasonicated in an ultrasonic cleaner for 15 minutes at room temperature to make it uniformly mixed, and then stirred by a magnetic stirrer for 1 hour to make it fully mixed.

[0031] It was then transferred to a high-pressure hydrothermal reactor and heated at 120°C for 2 hours. After the reaction was completed, it was cooled to room temperature and centrifuged at 8000 r / min for 10 minutes to separate the solid and liquid to obtain a solid sample of the composite material. The solid sample was then placed in an oven at 80°C and dried for 8 hours to finally obtain an NCDs / ZnFe2O4 nanocomposite material.

[0032] The structure and properties of the prepared ternary composite material NCDs / ZnFe2O4 were analyzed by characterization methods such as X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and X-ray photoelectron spectroscopy (XPS).

[0033] XRD results show that the XRD pattern of NCDs / ZnFe2O4 nanocomposites is almost the same as that of ZnFe2O4 nanoparticles, indicating that when NCDs are introduced into the / ZnFe2O4 nanocomposites, except for a slight increase in the peak intensity of NCDs / ZnFe2O4, there is no obvious difference in the crystal structure. This means that the addition of NCDs will not only not affect the structure of / ZnFe2O4, but also improve the crystallinity of the material.

[0034] FTIR results showed a sharp peak at 1652 cm-1 indicating the presence of amide bond -CONH-, which indicated that N was successfully doped into carbon dots to form NCDs. -1 The small peak at 447 cm indicates the presence of CH functional groups. In the NCDs / ZnFe2O4 composite, the peak of Fe-O bond shifts to 447 cm-1 The peak of Zn-O bond shifts to 581 cm -1 This may be due to the change in particle size and the change in metal-oxygen bond distance. -1 The peak found at 1637 cm-1 indicates the presence of an amide bond -CONH-, and the peak at 3440 cm-1 indicates the presence of a C=O bond. -1 The broad peak at is attributed to the stretching vibration of NH / -OH, which indicates that NCDs / ZnFe2O4 is successfully prepared.

[0035] The SEM results show that the elemental mapping of the sample in the figure shows the uniform distribution of each element, which further confirms the presence of the elements C, N, Zn, Fe and O. In addition, the distribution of the elements C, N, Zn, Fe and O is uniform, indicating that the NCDs are evenly dispersed on the ZnFe2O4 nanoparticles.

[0036] XPS results show that in the NCDs / ZnFe2O4 composite, the shift of binding energy to higher positions reflects the change of electron density outside O1s and C1s, which leads to the movement of electrons in NCDs and ZnFe2O4. The results prove the successful preparation of NCDs / ZnFe2O4 composite with high photocatalytic activity.

[0037] The above characterization methods confirm that the ternary composite material NCDs / ZnFe2O4 prepared in this example has good structure and performance.

[0038] In order to evaluate the application performance of the ternary composite material NCDs / ZnFe2O4 prepared in this example, its degradation effect on Rh B was tested.

[0039] In terms of catalyst stability, the NCDs / ZnFe2O4 composite nanomaterials were analyzed and tested using a cyclic experiment. The NCDs / ZnFe2O4 adsorbed with Rh B was extracted from the solution and retained for regeneration. Therefore, the solid was washed with ethanol several times to desorb the dye from the surface of NCDs / ZnFe2O4. The catalyst was then reactivated at 80°C and reused for the next catalytic experiment. The photocatalytic degradation efficiency after five cyclic experiments was 92.51%. This finding shows that NCDs / ZnFe2O4 has good cyclic stability.

[0040] [Example 2]

[0041] This embodiment provides a method for preparing a ternary composite material NCDs / ZnFe2O4, and the specific steps are as follows:

[0042] 1 g of citric acid solid was added to 10 mL of distilled water, and after ultrasonication for 5 min to completely dissolve it, the solution was transferred to a high-pressure hydrothermal reactor, and 335 μL of ethylenediamine solution was added. The reaction was then heated in an oven at 200 °C for 5 h. After the reaction was completed, the mixture was cooled to room temperature to obtain a dark brown NCDs suspension.

[0043] The NCDs suspension was filtered, washed twice with distilled water, and the filtrate was collected and placed in a 3500MW dialysis bag for continuous dialysis for 48 hours. Finally, the dialysate was freeze-dried to obtain a solid powder of the NCDs sample.

[0044] NCDs powder was added to the ZnFe2O4 aqueous solution to make the mass ratio be 1wt%. The mixture was ultrasonicated in an ultrasonic cleaner for 15 min at room temperature to make it evenly mixed, and then stirred by a magnetic stirrer for 1 h to make it fully mixed.

[0045] It was then transferred to a high-pressure hydrothermal reactor and heated at 80°C for 4 hours. After the reaction was completed, it was cooled to room temperature and centrifuged at 8000 r / min for 10 minutes to separate the solid and liquid to obtain a solid sample of the composite material. The solid sample was then placed in an oven at 80°C and dried for 8 hours to finally obtain an NCDs / ZnFe2O4 nanocomposite material.

[0046] [Example 3]

[0047] This embodiment provides a method for preparing a ternary composite material NCDs / ZnFe2O4, and the specific steps are as follows:

[0048] 1 g of citric acid solid was added to 10 mL of distilled water, and after ultrasonication for 5 min to completely dissolve it, the solution was transferred to a high-pressure hydrothermal reactor, and 335 μL of ethylenediamine solution was added. The reaction was then heated in an oven at 200 °C for 5 h. After the reaction was completed, the mixture was cooled to room temperature to obtain a dark brown NCDs suspension.

[0049] The NCDs suspension was filtered, washed twice with distilled water, and the filtrate was collected and placed in a 3500MW dialysis bag for continuous dialysis for 48 hours. Finally, the dialysate was freeze-dried to obtain a solid powder of the NCDs sample.

[0050] NCDs powder was added to the ZnFe2O4 aqueous solution to make the mass ratio of 5wt%. The mixture was ultrasonicated in an ultrasonic cleaner for 15 minutes at room temperature to make it uniformly mixed, and then stirred by a magnetic stirrer for 1 hour to make it fully mixed.

[0051] It was then transferred to a high-pressure hydrothermal reactor and heated at 140°C for 6 hours. After the reaction was completed, it was cooled to room temperature and centrifuged at 8000 r / min for 10 minutes to separate the solid and liquid and obtain a solid sample of the composite material. The solid sample was then placed in an oven at 80°C and dried for 8 hours to finally obtain an NCDs / ZnFe2O4 nanocomposite material.

[0052] [Example 4]

[0053] This embodiment provides a method for preparing a ternary composite material NCDs / ZnFe2O4, and the specific steps are as follows:

[0054] 1 g of citric acid solid was added to 10 mL of distilled water, and after ultrasonication for 5 min to completely dissolve it, the solution was transferred to a high-pressure hydrothermal reactor, and 335 μL of ethylenediamine solution was added. The reaction was then heated in an oven at 200 °C for 5 h. After the reaction was completed, the mixture was cooled to room temperature to obtain a dark brown NCDs suspension.

[0055] The NCDs suspension was filtered, washed twice with distilled water, and the filtrate was collected and placed in a 3500MW dialysis bag for continuous dialysis for 48 hours. Finally, the dialysate was freeze-dried to obtain a solid powder of the NCDs sample.

[0056] NCDs powder was added to the ZnFe2O4 aqueous solution to make the mass ratio of 7wt%. The mixture was ultrasonicated in an ultrasonic cleaner for 15min at room temperature to make it uniformly mixed, and then stirred by a magnetic stirrer for 1h to make it fully mixed.

[0057] Then it was transferred to a high-pressure hydrothermal reactor and heated at 140°C for 6 hours. After the reaction was completed, it was cooled to room temperature and centrifuged at 8000r / min for 10 minutes to separate the solid and liquid to obtain a composite solid sample. The solid sample was then placed in an oven at 160°C and dried for 10 hours to finally obtain the NCDs / ZnFe2O4 nanocomposite material.

Claims

1. A method for preparing a composite nanomaterial NCDs / ZnFe2O4 for degrading Rh B, characterized in that: The following steps are involved: ·Prepare NCDs by hydrothermal method to obtain solid powder of NCDs; ·Preparation of NCDs / ZnFe2O4 composite nanomaterials by hydrothermal method.

2. The method according to claim 1, characterized in that The carbon source selected was citric acid and the nitrogen source was ethylenediamine.

3. The method according to claim 1, characterized in that After the citric acid and ethylenediamine are mixed and reacted, the mixture is placed in a 3500MW dialysis bag and dialyzed for 48 hours, and then freeze-dried.

4. The method according to claim 2, characterized in that: NCDs with different weights were compounded with ZnFe2O4, with the weight ratios being 1wt%, 3wt%, 5wt% and 7wt% respectively.

5. The method according to claim 2, characterized in that: NCDs / ZnFe2O4 with different mass ratios were heated in a high-pressure hydrothermal reactor at 80°C, 100°C, 120°C, 140°C and 160°C, respectively.

6. The method according to claim 2, characterized in that The reacted sample was centrifuged at 8000 r / min for 10 min in a high-speed centrifuge to separate the solid and liquid and obtain a composite material solid sample.

7. The method according to claim 2, characterized in that: The solid sample was placed in an oven at 80°C and dried for 8 h to finally obtain the NCDs / ZnFe2O4 nanocomposite material.

8. Use of the nitrogen-doped carbon dots as claimed in claim 1 or the NCDs / ZnFe2O4 nanocomposite material prepared by the method as claimed in claim 2 in environmental management.

9. The use according to claim 10, characterized in that: Also includes: The NCDs / ZnFe2O4 nanocomposite material is used in degrading wastewater and organic pollutants.